Genotyping of Mycoplasma pneumoniae strains isolated in Japan during 2019 and 2020: spread of p1 gene type 2c and 2j variant strains - Kenri, Tsuyoshi; Yamazaki, Tsutomu; Ohya, Hitomi; Jinnai, Michio; Oda, Yoichiro; Asai, Sadasaburo; Sato, Rikako; Ishiguro, Nobuhisa; Oishi, Tomohiro; Horino, Atsuko; Fujii, Hiroyuki; Hashimoto, Toru; et al. (Frontiers in Microbiology, 2023)
We characterized 118 Mycoplasma pneumoniae strains isolated from three areas of Japan (Saitama, Kanagawa, and Osaka) during the period of 2019 and 2020. Genotyping of the p1 gene in these strains revealed that 29 of them were type 1 lineage (29/118, 24.6%), while 89 were type 2 lineage (89/118, 75.4%), thereby indicating that type 2 lineage was dominant in this period. The most prevalent variant of type 2 lineage was type 2c (57/89, 64%), while the second-most was type 2j, a novel variant identified in this study (30/89, 33.7%). Type 2j p1 is similar to type 2g p1, but cannot be distinguished from reference type 2 (classical type 2) using the standard polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP) with HaeIII digestion. Thus, we used MboI digestion in the PCR-RFLP analysis and re-examined the data from previous genotyping studies as well. This revealed that most strains reported as classical type 2 after 2010 in our studies were actually type 2j. The revised genotyping data showed that the type 2c and 2j strains have been spreading in recent years and were the most prevalent variants in Japan during the time-period of 2019 and 2020. We also analyzed the macrolide-resistance (MR) mutations in the 118 strains. MR mutations in the 23S rRNA gene were detected in 29 of these strains (29/118, 24.6%). The MR rate of type 1 lineage (14/29, 48.3%) was still higher than that of type 2 lineage (15/89, 16.9%); however, the MR rate of type 1 lineage was lower than that found in previous reports published in the 2010s, while that of type 2 lineage strains was slightly higher. Thus, there is a need for continuous surveillance of the p1 genotype and MR rate of M. pneumoniae clinical strains, to better understand the epidemiology and variant evolution of this pathogen, although M. pneumoniae pneumonia cases have decreased significantly since the COVID-19 pandemic.